2020
DOI: 10.1097/dbp.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Health and Neurodevelopment of Children Born to Opioid-Dependent Mothers at School Entry

Abstract: Objective: To examine the school readiness of a regional cohort of prenatally methadone-exposed children across 5 domains and to examine factors contributing to impairment risk. Methods: Data were drawn from a single-center, prospective longitudinal study. One hundred children born to women in methadone maintenance treatment and 110 randomly identified non–methadone-exposed children were studied from birth (2003–2008) to age 4.5 years. At 4.5 years, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Multivariable linear regression was used to determine which antenatal exposures were independently associated with neurodevelopmental outcomes, after accounting for patient characteristics and treatment modality. Covariates were chosen based on variables that infer impact on neonatal and later outcomes in this and other patient populations (23)(24)(25)(26). All models include race, sex, maternal age, private vs. public insurance, antenatal treatments, and prenatal exposures; all variables were retained in the model on clinical and theoretical grounds, regardless of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable linear regression was used to determine which antenatal exposures were independently associated with neurodevelopmental outcomes, after accounting for patient characteristics and treatment modality. Covariates were chosen based on variables that infer impact on neonatal and later outcomes in this and other patient populations (23)(24)(25)(26). All models include race, sex, maternal age, private vs. public insurance, antenatal treatments, and prenatal exposures; all variables were retained in the model on clinical and theoretical grounds, regardless of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we lacked socioeconomic data, information about maternal intelligence or education level, and environmental variables such as maternal nutrition and food insecurity, maternal mental health, consistency of prenatal care, trauma history, adverse childhood experiences, medical complications, and quality and stability of the child-rearing environment which all have a critical role in mediating long-term neurodevelopmental outcomes (9,11,17). Cognitive and language development are strongly influenced by early experiences, developmental stimulation, and stability of the social environment; the possibility remains that social environment may be more predictive of cognitive and language delays than prenatal exposures or neonatal NOWS treatment (9,17,26,(55)(56)(57)(58). However, it is most likely that a complex web of interconnected factors all influence development in this vulnerable population (9, 17, 57) Information about maternal intelligence, home environment, and postnatal caregiver was unavailable in our cohort; collecting this key information in future studies is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Lee, Woodward, and Henderson (2019) and Lee, Pritchard, Austin, Henderson, and Woodward (2020) observed that children born from opioid‐dependent women were at a high risk of educational delay/impairment. They suggested that this defect may be due to a fault in the neurodevelopment of children born from opioid‐dependent women.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages include more stable maternal drug levels, reduced withdrawal and drugseeking behavior, and improved self-care, which should lead to a better pregnancy outcome because of reduced risk for fetal distress, miscarriage, growth restriction, and preterm birth. 32 Compared to data on buprenorphine-maintained pregnancies, more longitudinal data on methadoneexposed pregnancies are available. In a prospective longitudinal study, 68 methadone-exposed children and 88 nonmethadone-exposed children were evaluated at 2.0 and 4.5 years for executive functioning and later emotional behavioral and emotional adjustment.…”
Section: Prenatal Opioid Use and Its Consequencesmentioning
confidence: 99%